Clinical validation of full genotyping CLART® HPV4S assay on SurePath and ThinPrep collected screening samples according to the international guidelines for human papillomavirus test requirements for cervical screening - Ejegod, Ditte Møller; Lagheden, Camilla; Bhatia, Ramya; Pedersen, Helle; Boada, Elia Alcañiz; Sundström, Karin; Cortés, Javier; Josë, F. Xavier Bosch; Cuschieri, Kate; Dillner, Joakim; Bonde, Jesper (BMC cancer, 2020)
Background To ensure the highest quality of human papillomavirus (HPV) testing in primary cervical cancer screening, novel HPV assays must be evaluated in accordance with the international guidelines. Furthermore, HPV assay with genotyping capabilities are becoming increasingly important in triage of HPV positive women in primary HPV screening. Here we evaluate a full genotyping HPV assay intended for primary screening. Methods The CLART® HPV4S (CLART4S) assay is a newly developed full-genotyping assay detecting 14 oncogenic (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68) and two non-oncogenic HPV genotypes (6, 11). It was evaluated using SurePath and ThinPrep screening samples collected from the Danish and Swedish cervical cancer screening programs, respectively. For calculation of sensitivity, 81 SurePath and 80 ThinPrep samples with confirmed ≥CIN2 were assessed. For clinical specificity analysis, 1184 SurePath and 1169 ThinPrep samples from women with <CIN2 histology were assessed. Sensitivity and specificity of the CLART4S assay was compared to an established reference test; the MGP-PCR (Modified General Primers GP5+/6+ with genotyping using Luminex). Inter and intra laboratory reproducibility of the assay was assessed using 540 SurePath and 520 ThinPrep samples, respectively. The genotype concordance between CLART4S and MGP-PCR was also assessed. Results In SurePath samples, the sensitivity of CLART4S was 0.90 (MGP-PCR =0.93) and the specificity was 0.91 (MGP-PCR = 0.91); In ThinPrep samples the sensitivity of CLART4S was 0.98 (MGP-PCR = 1.00) and specificity was 0.94 (MGP-PCR =0.87). The CLART4S was shown to be non-inferior to that of MGP-PCR for both sensitivity ( p = 0.002; p = 0.01) and specificity ( p = 0.01; p = 0.00) in SurePath and ThinPrep samples, respectively. Intra-laboratory reproducibility and inter-laboratory agreement was met for both media types. The individual genotype concordance between CLART4S and MGP-PCR was good agreement for almost all 14 HPV genotypes in both media types. Conclusions The CLART4S assay was proved non-inferior to the comparator assay MGP-PCR for both sensitivity and specificity using SurePath and ThinPrep cervical cancer screening samples from the Danish and Swedish screening programs, respectively. This is the first study to demonstrate clinical validation of a full-genotyping HPV assay conducted in parallel on both SurePath and ThinPrep collected samples.